Gatekeeping and gate-opening: Ethical and reflexive research with LESLLA stakeholders: A response to “Why should I care? Research ethics in the field of adult L2 literacy”. - Malessa, Eva; Playsted, Skye; Rillera Kempster, Jemima; Grinden, Live (Netherlands, 2026)
With their self-reflective article and vignettes, Shepperd and Dalderop provide valuable insights into their personal quest for ethical and reflexive research and make an important contribution to research ethics in applied linguistics. In our viewpoint, we would like to elaborate on their reflections on informed consent and voluntary participation by providing our thoughts on potential gate-openers/ gate-opening in LESLLA research. Their article considers three core areas of ethical care (consent, participation and minimising harm while optimising beneficence) to be exercised in LESLLA research and frames these as “layers of vulnerability” (see Luna, 2019). Similarly to Shepperd and Dalderop, we navigated these layers of vulnerability in our individual LESLLA research contexts in   Norway (Live), Australia (Skye and Jemima) and Finland (Eva) through various institutional and research gatekeepers and will discuss relevant personal and contextualized reflections of our own in this viewpoint.